An Analysis of Monoamine-Related Genotypes and Childhood Trauma in Relation to Psychopathic Traits in Men and Women. (September 2020) - Fox, Bryanna; Bozzay, Melanie; Verona, Edelyn
Psychopathy is of great interest to criminologists, given its consistent association with violence, offending, and antisocial behavior. However, the etiology of psychopathy, particularly in terms of a gene   ×   environment (G×E) interaction, has had little examination in the literature. One study has examined the direct and interactive effects of two genotypes (MAOA, 5-HTT) and childhood trauma on psychopathic traits using a high-risk forensic sample of adult males, and identified G×E interactions that may help us understand this complex phenotype. However, given the difficulties replicating G×E research, particularly with antisocial phenotypes, this study conducts a replication and expansion of prior research by examining direct and interactive effects of three genotypes (MAOA, 5-HTT, DRD4) and childhood trauma on psychopathy using a high-risk community sample of males and females. Results only partially support prior findings, illustrating the need for additional replication research in the biopsychosocial and epigenetic arenas.